The recording engineer's handbook - Owsinski, Bobby (Gale virtual reference library, 2005)
Everything you always wanted to know about tracking in stereo and surround, including advice from Grammy winning engineers. Includes sections on the history of classic microphones, condenser mic fallacies and getting the most from a vocalist, plus secrets of mic placement and choosing the right mic. There's also several different miking techniques for just about every instrument.